Methodical recommendation to "Basics of software engineering. Laboratory practice". Part 1 - Melnyk, K. V.; Borisova, N. V.; Lutenko, I. V.; Ershova, S. I.; Smolin, P. A.; Grinchenko, Marina Anatoliyvna (National Technical University "Kharkiv Polytechnic Institute", 2019)
Software engineering is an engineering discipline that is concerned with all aspects of software production. Software engineering can be divided into sub-disciplines. Some of them are: - Software engineering management: The application of management activities – planning, coordinating, measuring, monitoring, controlling, and reporting – to ensure that the development and maintenance of software is systematic, disciplined, and quantified. Requirements engineering: The elicitation, analysis, specification, and validation of requirements for software.
Keywords: calculation of formulas; modeling of domain; coding of domain; individual tasks; reference list